Superdosagem de fitase para frangos de corte e poedeiras leves - Lima, Guilherme Souza (2018)
The processes for obtaining the phytase enzymes vary and may be carried out basically in two ways, either by solid-state fermentation (SET) or by submerged fermentation (SF). Both processes present advantages and disadvantages according to the initiation site of phytate dephosphorylation, catalytic mechanism and pH activity. In this sense, there are three types of phytases classified based on the specific position of initial phytate hydrolysis: 3-phytase, 4-phytase or 6-phytase, and 5-phytase. These enzymes may be classified based on their catalytic properties: acidic histidine phosphatases (AHP), β-helix phytases (BHP), purple acid phosphatases (PAP) cysteine phosphatase (CP), and a last classification is made according to the pH, in acids and alkalis enzymes. Phytase acts directly on the phytate molecule releasing phosphorus, however phytase superdosing in feed provides results that go beyond phosphorus availability and can improve overall performance and nutrient utilization efficiency, thus increasing production efficiency for poultry systems. In order to evaluate the action of superdosing phytase, two experiments were carried out on broilers and commercial laying hens. The objective of this study was to evaluate the supplementation of phytase superdosing in diets with reduction of amino acid levels for broilers from 1 to 45 days under the parameters of performance, carcass characteristics, intestinal morphometry and ileal digestibility. We evaluated 1848 male broilers of the COBB 500 strain divided into 12 treatments. The animals were distributed in a completely randomized design in a 3x4 factorial scheme (three nutritional matrices with 0, 5 and 10% reduction in digestible methionine, lysine and threonine amino acid levels), and four phytase levels (0, 500, 1500 and 3000 FTU/kg), seven replicates of twenty-two birds per experimental unit. For the ileal digestibility, a separate experiment was set up following the same experimental design, however 252 animals were distributed in 12 treatments, 3 replicates of 7 birds each. After phytase supplementation at 1500FTU/kg, it is possible to reduce by up to 10% the levels of the first three limiting amino acids for broilers from 1 to 45 days without affecting performance of the animals. Phytase superdosing promoted a greater availability of phosphorus and improvement in the digestive tract of birds, increasing the ratio villus: crypt, as well as the villi area. These factors are related to cell proliferation, intestinal health and absorption of nutrients. It is recommended to reduce the Ca and P levels of the diets, valuing the availability of these minerals by the enzyme matrix, and the supplementation of 1500 FTU/kg of bacterial phytase. This superdosing allowed the reduction of up to 10% in the supplementation of the amino acids methionine, lysine and threonine in the diet of broilers. For the experiment with commercial laying hens the objective was to evaluate the exogenous phytase supplementation in an superdosing for light laying hens in the second production cycle. A total of 320 light laying hens of the Hy-line W-36 strain, aged 44 to 64 weeks, were divided into five treatments in a completely randomized design with eight replicates and eight birds each. The diets were formulated to meet the requirements of the birds based on the breeding manual being isoproteic and isoenergetic. To meet the levels of 0, 500, 1000, 1500 and 3000 FTU/kg, the inert was replaced with doses of the phytase enzyme in the following ratios of zero, 0.100; 0.200; 0.300 and 0.600 kg/ton. The variables analyzed were poultry performance and egg quality, intestinal morphometry and magnum epithelium, glycogen concentration and degree of hepatic steatosis, and number of folds in uterus. Differences were observed between the levels of phytase supplementation with quadratic model adjustment for the variables: egg mass (g), egg mass (g/bird/day), feed conversion (g/g of egg mass), yolk concentration (%), albumen concentration (%), thickness (μm), and bark resistance (kgf), specific gravity and yolk color. The increasing levels of phytase supplementation allowed the improvement of the digestive tract of the birds providing a better relationship villus:crypt. The thickness of the magnum epithelium (μm) was linear, so, in the highest level of phytase supplementation the magnum epithelium was thicker. Phytase superdosing provides greater energetic reserves in the liver and uterus with greater amount of secondary and tertiary folds characterizing a better organ efficiency. The superdosing made it possible for steatosis grade 1 to appear. Therefore, for verifying the beneficial effects of superdosing it is recommended to supplement 1500 FTU/kg of bacterial phytase in corn and soybean meal diets for light laying hens from 44 to 64 weeks of production.